2019
DOI: 10.1177/0950422219874703
|View full text |Cite
|
Sign up to set email alerts
|

Are we teaching what employers want? Identifying and remedying gaps between employer needs, accreditor prescriptions, and undergraduate curricular priorities

Abstract: Employers and policy makers have criticized higher education institutions for the perceived knowledge and skills deficiencies of their graduates. This article seeks to identify the gaps between employer needs, curricular priorities, and accrediting standards, specifically in the management domain. To this end, the authors content analyzed 200 job announcements for entry-level management positions in the 10 largest metropolitan statistical areas in the United States and the learning goals of 51 busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…There is an increasing consensus that marketing practitioners are important stakeholders in marketing education, and that a major role for universities is to equip graduates with the right knowledge and skills for employment (Rhew et al, 2019;Ye et al, 2017). The divide between what is taught in the curriculum and marketplace requirements has long been observed in the literature (Duffy & Ney, 2015;McArthur et al, 2017), with some calling for a shift toward a pracademic paradigm where practice and skill development is prioritized over theories (McNatt et al, 2010).…”
Section: The Theory-practice Gap In Marketing Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an increasing consensus that marketing practitioners are important stakeholders in marketing education, and that a major role for universities is to equip graduates with the right knowledge and skills for employment (Rhew et al, 2019;Ye et al, 2017). The divide between what is taught in the curriculum and marketplace requirements has long been observed in the literature (Duffy & Ney, 2015;McArthur et al, 2017), with some calling for a shift toward a pracademic paradigm where practice and skill development is prioritized over theories (McNatt et al, 2010).…”
Section: The Theory-practice Gap In Marketing Educationmentioning
confidence: 99%
“…Live project-based learning could be used by educators to successfully develop students' soft skills and technical skills (Rohm et al, 2021). The value of experiential and live project-based learning in bridging the theory-practice gap (Spiller & Tuten, 2019;Wilson et al, 2018;Ye et al, 2017), as well as developing these soft skills through real-world projects or work placements (Rhew et al, 2019;Rohm et al, 2019) has been demonstrated.…”
Section: Soft Skills Are Fundamentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of job advertisements as a data source is well established, although there is little guidance available on how best to collect and analyze these data (Harper, 2012). A search of the graduate employability literature has revealed a number of studies that have used job advertisements to gauge what employers require of graduates in the workplace, including for marketing (Bennett, 2002; McArthur et al, 2017; Wellman, 2010); general management, finance and human resource management (Bennett, 2002; Rhew et al, 2019); sport marketing, ticket sales and sponsorship sales (Bae and Miller, 2011; Diamond et al, 2014; Pierce et al, 2012); recreation and tourism (Crossley, 1992; Keung and Pine, 2000); library and information science (Clyde, 2002); information technology (Todd et al, 1995); project management (Ahsan et al, 2013); and event management (Arcodia and Barker, 2002). A search of the literature failed to turn up any such studies for jobs in the environmental sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with a good technical knowledge industry also demands a set of skills which are necessary for better performance of an employee in the described job profile. (Nicholas D. Rhew, 2019)An engineer needs different managerial skills as well as various technical skills. Skill sets required by the various types of industries differ at each level.…”
Section: Introductionmentioning
confidence: 99%